BLUEPRINTING FOR SUMMATIVE THEORY ASSESSMENT IN COMMUNITY MEDICINE FOR UNDERGRADUATE MEDICAL STUDENTS. - Pinto Violet N; Mammen Sheena A; Joshi Sumedha M; Rao Rajiv J (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Context: Competency-based medical education emphasizes outcome-driven learning and requires robust assessment to ensure students achieve the defined competencies required by an Indian Medical graduate. The study aims to prepare a blueprint for summative theory assessment in Community Medicine for undergraduate MBBS students.Material and methods: Study was conducted at a private medical college in Navi Mumbai. Steps involved in preparation of blueprint were followed including listing of subject topics, marks allocation, assigning impact and frequency factors, calculation of topic weightage and integrating Bloom’s taxonomy. The suggestions from experts were reviewed and changes were made.Results: A comprehensive blueprint was prepared integrating Bloom’s taxonomy (recall, comprehension, analysis, application) across questions of both papers. Certain topics like Epidemiology of Communicable and Non-communicable diseases, Emerging/re-emerging infections, Epidemiological principles, National health programs, Health care of community, MCH and Nutrition with higher I and F factors, teaching hours had proportionally more marks weightage.Conclusions: The developed blueprint offers a structured framework for assessment including proportional topic representation according to public health importance and application in clinical practice.